El impacto de la inteligencia artificial en la legislación laboral y cómo deben evolucionar las leyes para adaptarse a este nuevo contexto - Martinez Armijos, John Paul (2024)
The present work on Curricular Integration addresses the lack and clear regulations that the labor system faces in the country with the lack of regulation of the same, therefore my work aims to provide and protect the guarantees of the workers against their uncertainty. lose their job when AI is implemented incorrectly in the workplace. While it is true that technology has become a means of helping to improve even education, it is also true that society is being affected because it is increasingly easier to replace human labor with mechanical and computer labor. , it is not strange to know that nowadays it is easier to understand a pre-recorded video than the instructions given by a teacher, as well as to enter a public company's website and have its virtual assistant immediately solve a problem and thus avoid agglomeration, as it is also normal to see a robot that assembles vehicles much faster than a human being, or that the use of machinery accelerates the production of processed products than the speed with which a person would produce it. However, let us not forget the pandemic that the world experienced as a result of Covid-19, thanks to this sanitation problem, several companies were forced to adopt the use and increase of technological tools as a help measure on several occasions as a measure to solve the situation that the country suffered, which to a large extent progress was made in the construction of innovations but on some occasions the guarantees of workers were destroyed, thus violating their rights, which must safeguard the rights of workers as priority of these.